2015
DOI: 10.1021/acs.accounts.5b00051
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Couplings Using Aryl Ethers via C–O Bond Activation Enabled by Nickel Catalysts

Abstract: Arene synthesis has been revolutionized by the invention of catalytic cross-coupling reactions, wherein aryl halides can be coupled with organometallic and organic nucleophiles. Although the replacement of aryl halides with phenol derivatives would lead to more economical and ecological methods, success has been primarily limited to activated phenol derivatives such as triflates. Aryl ethers arguably represent one of the most ideal substrates in terms of availability, cost, safety, and atom efficiency. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
240
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 608 publications
(247 citation statements)
references
References 63 publications
4
240
0
3
Order By: Relevance
“…[51][52][53][54] Martin and colleagues reported that direct OA of a E C-O bond to Ni(0) requires high temperature, based on experimental and theoretical findings. 46) Computational studies by Nakamura and colleagues, 55) Liu and colleagues, 56) Martin and colleagues, 46) and us 14) clearly demonstrated that OA of a E C-O bond generally involves a very high activation barrier (Chart 2(1)), even considering the Lewis acidity of Mg (Chart 2 (2)). This could be attributed to the high stability of the E C-O bond and the weak interaction between the E C-O moiety and Ni(0) species.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…[51][52][53][54] Martin and colleagues reported that direct OA of a E C-O bond to Ni(0) requires high temperature, based on experimental and theoretical findings. 46) Computational studies by Nakamura and colleagues, 55) Liu and colleagues, 56) Martin and colleagues, 46) and us 14) clearly demonstrated that OA of a E C-O bond generally involves a very high activation barrier (Chart 2(1)), even considering the Lewis acidity of Mg (Chart 2 (2)). This could be attributed to the high stability of the E C-O bond and the weak interaction between the E C-O moiety and Ni(0) species.…”
Section: Resultsmentioning
confidence: 96%
“…Based on this work, together with our previous mechanistic study on etheric Kumada-Tamao reaction, we identify and characterize a novel catalytic cycle for cross-coupling mediated by Ni(0)-ate complex.Key words cross-coupling; ether; nickel catalyst; organolithium; organozinc; density functional theory (DFT) calculation Efficient and selective cleavage and transformation of C-O bonds, particularly by means of cross-coupling methods, has attracted great interest, since compounds containing C-O moieties occur widely in nature and are also extensively utilized in industry.1-8) Among C-O compounds, ethers are particularly attractive, [1][2][3][4][5][6][7][8] as they offer the advantages of 1) high atom economy/conversion efficiency (the use of ethers as simple as MeO as substrates affords fewer by-products compared with tosylate, mesylate, triflate, phosphate, etc. ), 2) environmental compatibility (cleavage of the C-O moiety in ether releases non-halogen-containing waste), and 3) excellent stability, easy accessibility and wide diversity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we established the direct conversion of 3G to aniline derivatives (Fig. 6c) through homogeneous nickel-catalysed crosscoupling 34,35 using a variety of amines and pseudohalogenide 8 that was obtained from 3G. Gratifyingly, 8 underwent cross-coupling with a number of amines to yield the corresponding aromatic products 9a-9e.…”
Section: Nature Catalysismentioning
confidence: 99%
“…Catalytic transformations via alkenyl [17][18][19][20][21][22][23][24][25][26][27][28] and benzylic C-O bond [29,30] activation are not covered. In addition, readers are encouraged to consult previous reviews on catalytic C-O bond activation reactions [31][32][33][34][35][36][37][38]. …”
Section: Introductionmentioning
confidence: 99%